Innovative Negotiation Strategies for Achieving Win-Win Outcomes - Zhang, Haiming (Transactions on Economics, Business and Management Research, 2024)
Negotiation is a communication process between two or more organizations or individuals, in which they discuss, negotiate, and strive to reach a consensus or agreement. The purpose of this process is diverse, including establishing connections, resolving common issues, handling conflicts and disputes, and improving relationships between each other. At the same time, this is also a process of meeting the needs of all parties. With the continuous advancement of globalization, communication between countries has become increasingly frequent, and business negotiations have become more and more common as a result. However, it is worth noting that despite the increasing number of business negotiations, it is not always easy to reach an agreement through negotiation. This usually requires significant effort from all parties, demonstrating sincerity, and employing skilled negotiation skills. This article aims to analyze commonly used techniques in business negotiations, identify the most suitable method for both parties to reach an agreement, and achieve a win-win situation.